Biochemistry of Lipids, Lipoproteins, and Membranes;vol-36. - Vance, Dennis E;Ed. Vance, Jean E;Ed (New comprehensive biochemistry, 2002)
Provides information on the advances in the field of lipid biochemistry. This book provides a summary of diverse aspects of lipids. It is intended as an advanced textbook for teachers and students who are familiar with the basic concepts of lipid biochemistry. It is also suitable for scientists studying lipids, lipoproteins and membranes.